Enzymatic one-pot synthesis of renewable and biodegradable surfactants in supercritical carbon dioxide (scCO2). Issue 4 (30th January 2020) - d'Almeida Gameiro, Mariana; Goddard, Amy; Taresco, Vincenzo; Howdle, Steven M.
Abstract : We exploit enzymatic catalysis in supercritical carbon dioxide to create novel, linear and degradable amphiphilic polymers that can act as surfactants. Abstract : We seek to expand the opportunities to exploit glycerol, a largely untapped renewable feedstock, by exploiting enzymatic catalysis in supercritical carbon dioxide (scCO2 ). This work highlights a promising and clean approach to bio-renewable amphiphilic polyester-based biodegradable surfactants. We have developed a low temperature (40, 50 and 60 °C), low energy melt processing route to biodegradable, renewable poly(glycerol succinate) (PGLSA) polymers that importantly have a low degree of branching (3% < DB < 11%). Our approach shows significant advantages over traditional melt polycondensation at 110–120 °C, where the standard catalyst-free approach led only to highly branched (DB > 85%) or insoluble crosslinked materials. We have exploited these linear PGLSA materials to create a library of ' green ' surfactants by end-capping with lauric acid or poly(ethylene glycol). Our approach avoids pre-modification of the monomers and fewer synthetic steps are required. Finally, we evaluate the performance of these new surfactants, focussing upon surface tension, critical aggregation concentration (CAC) and water contact angle.